EFFECT OF POPULATION GRWTH ON ECONOMIC GROWTH IN IRQ UNDER THE CHALLENGES OF SUSTAINABLE DEVELOPMENT - Mustafa Kamel Rashid; Suhaila Abdul-Zahra Mastour (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Most countries of the world tend to determine population growth in order to properly direct economic resources, in order to avoid pressure on these resources and their depletion, and then economic growth declines, and sustainable development plans falter.The study aims to measure the impact of population growth on economic growth in Iraq, because Iraq after 2003 witnessed dangerous economic developments, and a turbulent political environment that caused wastage of financial resources, despite the security and social instability, Iraq witnessed a significant increase in population growth. a problem statement is that the continued increase in population growth will lose the possibility of controlling natural resources and thus economic growth.The hypothesis of the study is that population growth constitutes a major challenge to reforming output and then economic growth, which impedes economic development plans.The importance of the study is that determining population growth is a necessity in order to reduce pressure on financial and natural resources, if Iraq witnessed during the period (2004-2018) a significant increase in aggregate demand due to the high population abundance, despite the poor services, education and health, and the ongoing battles with ISIS gangs, which claimed Hundreds of people were killed.The study concluded that population growth significantly affects the long-term economic growth in Iraq.The study recommended taking care of human capital, and employing it in order to serve local production and then economic growth, which serves sustainable development plans.